Good pope, bad pope : their lives, our lessons - Aquilina, Mike. (Cincinnati, Ohio : Servant Books, 2013)
"Why did the author pick the popes you'll meet in the pages of this book? Why not Gregory I, whom many would call the greatest pope of all time? Why not Leo X, who was pope at the beginning of the Protestant Reformation? Why not Leo XIII, who boldly stood up for the rights of workers? Every pope is by definition a remarkable man. But the popes whose stories you'll read here were chosen because they reveal how the papacy developed. They show us how Christ kept his promise to his bride, the Church, not only in her health but also in her sickness. The great popes advanced our understanding of Christian doctrine. But even more remarkable, the worst popes could do nothing to damage the teaching of the Church. That's why, even in its darkest moments, the story of the papacy is a story of triumph. And that's why it's worth knowing these twelve popes"--
St. Peter the Apostle (32-67) -- St. Clement (First Century) -- Liberius (352-356) -- Damasus (366-384) -- St. Leo the Great (440-461) -- Vigilius (537-555) -- Benedict IX (1032-1045) -- St. Celestine V (1294) -- Alexander VI (1492-1503) -- St. Pius V (1566-1572) -- Pius XII (1939-1958) -- John Paul II (1978-2005).
Includes bibliographical references (pages 134-136).
Description based on print version record.
Keywords: Papacy -- History; Popes -- Biography; RELIGION / Clergy; RELIGION / Christian Church / Leadership; RELIGION / Christianity / Catholic; Papacy; Popes; Biography; History; Electronic books